Prevalence of Beta Thalassemia Trait and Its Association with Hematological Parameters in Local Population of Rawalpindi & Islamabad, Pakistan - Muhammad Ilyas, Zakir Ahmad, Muhammad Umar Nafees, Arsalan Waqas Ahmad Shah, Noor Zada Khan, Ahmad Iqbal, Irfan Mahmood, Adnan Ahmad, Fawad Inayat (Drugs and Cell Therapies in Hematology, 2021)
Thalassemia is a group of hereditary blood diseases characterized by abnormal synthesis of the hemoglobin chain, resulting in a variable phenotype, ranging from severe anemia to clinically asymptomatic individuals. The main purpose and aim of this study are to find out the prevalence rate of beta-thalassemia in the local population of Rawalpindi/Islamabad and to find out its association with several hematological parameters that are involved in the screening tests for thalassemia. A Hospital-based retrospective cross-sectional study was performed, and data were collected from the hematology department of holy family hospital Rawalpindi. In this descriptive study, Hemoglobin levels, RBC count, HCT, MCV and MCH were measured in the suspected cases of β-thalassemia which were further confirmed by performing their HB Electrophoresis. A total of 60 patients from different regions of twin cities were tested during this time. Amongst which 14 were identified as carriers of β-thalassemia with their blood cell indices observed as lower than normal. The study revealed that the prevalence of β-thalassemia in twin cities is around 2.3%. Hence, we conclude that the mentioned indices and parameters have the highest sensitivity in the preliminary detection of thalassemia trait patients in our population. They can be used as cheap and quick tests for initial screening of patients in high prevalence areas where either advanced investigation tools are not available, or in low socio-economic families who cannot afford high-cost investigations. The patients identified can then be referred for specialized tests.